High Precision Self-Mixing Interferometer Based on Reflective Phase Modulation Method - Liping Lu (IEEE, 2020)
In this paper, a novel self-mixing interferometer based on reflective phase modulation (RPM) method has been developed to perform micro-displacement reconstruction with nanometer accuracy. Broaden harmonic components spectrum of the self-mixing signal is produced by employing a high-frequency vibrating reflective mirror as the phase modulation device. Phase demodulation is implemented applying the orthogonal demodulation algorithm subject to the signal spectrum, in which orthogonal signal can be extracted from the harmonic components of the expanded Bessel function. The principle and signal processing approach are introduced in detail, and the simulation results indicate that the reconstruction error can be reduced as the number of reflections increases. A series of experiments at different vibration amplitudes show that the reconstructed errors are all less than 10 nm with modulation frequency of 1 kHz. And the minimum error of 3 nm has been achieved at the measured amplitude of 229 nm, which demonstrates the technical-superiority and high-performance of the method.